Meteorological observations at Bayelva Station in 2024 (level 1) - Julia Boike; Inge Grünberg; Frederieke Miesner; Niko Bornemann; William L Cable (PANGAEA, 2025)
Understanding permafrost processes and changes requires long-term observational datasets. This dataset is a continuation of the dataset available from the Bayelva Site at Ny-Ålesund, Svalbard, where meteorology, energy balance components and subsurface observations have been made for more than the last 20 years. The data provide observations of temporally variable parameters that mitigate energy fluxes between permafrost and atmosphere, such as snow depth, snow dielectric number, snow temperature, liquid precipitation, air temperature, relative humidity, wind speed and direction and radiation fluxes. They are suitable for use in integrating, calibrating and testing permafrost as a component in Earth System Models. The resulting quality-controlled dataset is unique in the Arctic and serves as a baseline for future studies.
In: Boike, J et al. (2022): Continuous measurements in soil and air at the permafrost long-term observatory at the Bayelva station near Ny-Ålesund (2018 et seq) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.948951